The U.S. - Israeli annexation plan of the 21st century - Omar, Rusdi; Slimia, Awad; Khamis, Kamarul Azman; Islam, Rabiul (Allied Business Academies, 2021)
During the years of mediation between Israelis and the Palestinians, the desires, restrictions, and stability of Israel have always been the top U.S. priorities. However, the successive the U.S. administrations have decided that the peace process e.g., a viable Palestinian state besides Israeli state, even though if they are reluctant. Yet, while a lasting settlement appeared feasible once, nearly 30 years ago. A series of secret talks in Norway became the peace process in Oslo, symbolized forever by a 1993 White House lawn ceremony presided over by a beaming President Bill Clinton. But President Trump is not missing any opportunity to boast about the power of America. He thinks the military and economic strength of America allows him to impose his will. With his “Century Deal” strategy, he wants to break U.N. peace efforts to settle Israeli-Palestinian dispute. In this paper, the authors argue that the annexing Israeli illegal settlements in the West Bank, along with the Jordan Valley. It would amount to the Israeli state stealing Palestinian land and smashing any hopes of a two-state solution to the conflict between Israel and Palestine.